Tax Morale and Tax Evasion: Social Preferences and Bounded Rationality - Zsombor Z. Méder; András Simonovits; János Vincze (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2012)
We study a family of models of tax evasion, where a flat-rate tax finances only the provision of public goods, neglecting audits and wage differences. We focus on the comparison of two modeling approaches. The first is based on optimizing agents, who are endowed with social preferences, their utility being the sum of private consumption and moral utility. The second approach involves agents acting according to simple heuristics. We find that while we encounter the traditionally shaped Laffer-curve in the optimizing model, the heuristics models exhibit (linearly) increasing Laffer-curves. This difference is related to a peculiar type of behavior emerging within the heuristics based approach: a number of agents lurk in a moral state of limbo, alternating between altruism and selfishness.
Keywords: H26; 330; tax evasion; tax morale; agent-based simulation; Flat Tax; Öffentliche Güter; Steuervermeidung; Steuermoral; Laffer-Kurve; Begrenzte Rationalität; Agentenbasierte Modellierung; Theorie